Formula Madu Untuk Mengatasi Diare Pada Balita Di Puskesmas Wanadadi 1 Banjarnegara: Studi Kasus - Yuni Nur Indriani; Fauziah Hanum NA; Linda Yanti (Universitas Nazhatut Thullab Al- Muafa Sampang, 2022)
Introduction: Diarrhea cases are generally more dominant in children under 5 years of age or toddlers because their physical condition is still weak and they are easily infected with the spread of bacteria that cause diarrhea. If not treated immediately, it can cause death. The purpose of this study was to determine the effectiveness of giving honey formula to toddlers with diarrhea without dehydration. Case Presentation: We report a case of diarrhea without dehydration in toddler An. G aged 1 year 5 months 21 days who came to the health center with good general condition, weight 9.3 kg, abdominal bloating, and increased bowel sounds auscultation. Conclusion: Honey formula is more effective in dealing with diarrhea in toddlers, after consuming honey within 24 hours there is a change in the consistency of the stool to become denser, the frequency of defecation decreases and the general condition of children under five is getting better. Suggestion: Giving formula honey to toddlers with diarrhea is very good if you don't consume excessively and know the dose, which is given for 5 days with a dose of 5 cc/1 teaspoon of honey and given 3 times a day every 8 hours.